Não adesão ao paradigma psicossocial da saúde mental: papel dos estereótipos, crenças, percepção de ameaça e preconceito - Sousa, Patrícia Fonseca de (2020)
The Psychiatric Reform seeks to replace the biomedical paradigm by the psychosocial one, however, there are difficulties in implementing this proposal. This thesis aims to propose an explanatory model of non-adherence to the psychosocial paradigm based on stereotypes, beliefs about the etiology of mental illness, the perception of threat and prejudice. The thesis defended is that non-adherence to the psychosocial paradigm is associated with the permanence of prejudice and the perception of threat to the mentally ill, who are anchored in beliefs about the etiology of mental illness and in negative stereotypes. In order to achieve the proposed objective and confirm or refute the defended thesis, four studies were prepared in article format. Article 1 is a theoretical review that addresses the contributions of stereotypes, beliefs about the etiology of mental illness, perception of threat and prejudice in explaining non-adherence to the psychosocial paradigm. It was identified that the constructs analyzed are important in determining intergroup actions and, therefore, can contribute to the understanding of non-adherence to the psychosocial paradigm. Article 2 aimed to understand the social representations of mental health professionals, health university students and high school students about the crazy and mentally ill, relating them to mental health care paradigms (biomedical and psychosocial). 150 people participated, 50 from each social group. For data collection, the Free Word Association Technique (stimuli: crazy and mentally ill) was used. The data were analyzed using the Tri-Deux-Mots. High school students and university students presented representations of the madman and the mentally ill anchored in the biomedical paradigm, while professionals presented representations anchored in the psychosocial paradigm. The purpose of article 3 was to develop the Scale of Stereotypes about the Mentally Ill, gathering psychometric evidence, two studies were carried out. In Study 1, 210 university students participated and exploratory factor analyzes indicated the existence of two components (Threat Stereotypes, α = 0.81; Disability Stereotypes, α = 0.80) with 10 items in total. In Study 2, 206 university students participated and a confirmatory factor analysis indicated that the proposed two-factor model was adequate: χ² / gl = 2.31, GFI = 0.93, CFI = 0.94 and RMSEA = 0.08 (CI 90% = 0.057 - 0.103). Article 4 aimed to propose an explanatory model of non-adherence to the psychosocial paradigm of mental health based on stereotypes, beliefs about the etiology of mental illness, perception of threat and prejudice. 400 university students participated, who answered: Scale of Beliefs about Mental Illness; Scale of Stereotypes about the Mentally Ill; Threat Perception Scale for Mentally Ill; Scale of Prejudice against the Mentally Ill and Scale of Attitudes in Mental Health. The results showed that the higher the perception of threat and the agreement with the disability stereotype, the lower the support for the psychosocial paradigm. Furthermore, it was found that beliefs and stereotypes are at the basis of the perception of threat and all these variables together predict greater prejudice. The findings contribute to the understanding of the factors that may favor the effectiveness of the psychosocial paradigm in the mental health scenario and adherence to the precepts of Psychiatric Reform.